2022
DOI: 10.3389/fnagi.2022.822350
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Uric Acid Increases the Risk of Ischemic Stroke Recurrence and Its Inflammatory Mechanism in Older Adults

Abstract: BackgroundSerum uric acid (UA) has been reported to be associated with ischemic stroke and inflammation. However, whether or not UA is related to the recurrence of ischemic stroke, and whether inflammation plays a role in the relationship between them remain inconclusive.ObjectiveWe sought to explore the relationship between UA and the recurrence of ischemic stroke and to define the role of neutrophil-to-lymphocyte ratio (NLR) in the aforementioned relationship.MethodsA total of 8,995 patients were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…Experimental studies have shown that increased SUA as a pro‐oxidant is associated with endothelial dysfunction, increased oxidative stress, elevated plasma renin activity and systemic inflammation mediators, which may contribute to the development of HS 36,37 . Population study found that elevated serum uric acid increases the risk of stroke recurrence 38 . On the other hand, SUA is also an abundant natural antioxidant capable of reducing cellular oxidation, a major cause of neurodegenerative disease 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that increased SUA as a pro‐oxidant is associated with endothelial dysfunction, increased oxidative stress, elevated plasma renin activity and systemic inflammation mediators, which may contribute to the development of HS 36,37 . Population study found that elevated serum uric acid increases the risk of stroke recurrence 38 . On the other hand, SUA is also an abundant natural antioxidant capable of reducing cellular oxidation, a major cause of neurodegenerative disease 39 .…”
Section: Discussionmentioning
confidence: 99%
“…10 Retrospective research suggested that uric acid was related to stroke recurrence in older adults with interaction to inflammatory factors. 27 Packer et al proved that uric acid could increase the production of reactive oxygen species and enhance oxidative stress. 28 However, uric Abbreviations: CI, confidence interval; HR, hazard ratio; SUA/SCr, serum uric acid/serum creatine.…”
Section: Discussionmentioning
confidence: 99%
“…As a metabolite, SUA also carries a risk of contributing to development of diabetes ( Lu et al, 2020 ), and diabetes increases the risk of dementia ( Biessels and Despa, 2018 ). It has also been demonstrated that hyperuricemia is a risk factor for cerebrovascular ( Zhu et al, 2022 ) and cardiovascular illnesses ( Mouradjian et al, 2020 ). Further, vascular risk factors have been linked to an increased risk of dementia ( Gottesman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the subgroup analysis stratified by age, gender, and race, the model is not adjusted for age, gender, or race, respectively. factor for cerebrovascular (Zhu et al, 2022) and cardiovascular illnesses (Mouradjian et al, 2020). Further, vascular risk factors have been linked to an increased risk of dementia (Gottesman et al, 2017).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%